(untitled) (International Journal of Environmental Sciences, 2025)
This study investigated the influence of demographic factors (gender and academic stream) on learning styles (cognitive, affective, and psychomotor) among 167 higher secondary students in West Tripura District. Using independent samples t-tests and one-way ANOVA, the results revealed no significant gender differences across all three learning style dimensions (p > 0.05). However, significant differences emerged in cognitive learning styles across academic streams (F = 3.64, p = 0.030), with science students (M = 60.3) scoring significantly higher than commerce students (M = 56.6). No significant stream differences were found for affective or psychomotor learning styles. These findings suggest that while gender does not influence learning style preferences, academic stream selection may be associated with certain cognitive learning approaches, though the causal direction remains unclear.